Breaking the germline barrier in a moral vacuum. (18th August 2019) - Krimsky, Sheldon
ABSTRACT: In November 2018 a Chinese scientist claimed to have used CRISPR/Cas 9 technology to genetically modify two human embryos that were then gestated in one adult woman through an IVF pregnancy and brought to term. The twin girls are allegedly the first babies born with their prenatal genomes edited. Using both English language and Chinese supporting documents, this paper discusses the background of this human experiment, the social context of Chinese science, and the alleged ethical transgressions of its principal scientist.